Strategi Guru Pendidikan Agama Islam dalam Pembinaan Akhlak Mahmudah di Sekolah Menengah Pertama - Atika Robiatul Adawiyah; Siti Rofiqoh At-Thobibi; Rochmatus Saidah (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2026)
Purpose: This study aims to analyze the strategies employed by Islamic Education (PAI) teachers in fostering akhlaq mahmudah (noble character) among seventh-grade students at SMPN 11 Pasuruan City. Design/methodology/approach: The research uses a qualitative approach with a case study design. Data were collected through observations, interviews, and documentation involving PAI teachers, students, and school administrators. Findings: The results indicate that teachers implement various strategies, including role modeling (uswah hasanah), habituation of positive behaviors, integration of moral values into learning activities, and providing advice and motivation. In addition, teachers collaborate with parents and utilize religious activities such as congregational prayers and Qur'an recitation programs to strengthen students' character development. The findings reveal that these strategies significantly contribute to shaping students' discipline, honesty, responsibility, and respect toward others. Research limitations/implications: Challenges such as diverse student backgrounds and the influence of external environments remain obstacles in the implementation process. Therefore, continuous collaboration among teachers, parents, and the school environment is essential to optimize the development of students' noble character. Originality/value: This research provides empirical insights into the integration of multiple character-building strategies in a junior high school context, highlighting the combined role of teacher exemplar, habituation, and school-family collaboration in fostering Islamic moral values.